The Influence of Social Training on the Social Skills of Sport Pedagogues - Malinauskas, Romualdas (Acta Paedagogica Vilnensia, 2004)
The factors of social skills of sport pedagogues are researched not sufficiently enough. The problem of the research work is that data, which would reveal the level of social skills of sport pedagogues, is still leaking. The objective of the work is to define the influence of social training on the social skills of sport pedagogues (basing on the experience of Lithuanian Academy of Physical Education). The subject of the research is the level of social skills of sport pedagogues. The research was based on questionnaire (24-item Social Skills Inventory). The Social Skills Inventory was generated after providing an exploratory survey at Lithuanian Academy of Physical Education. The Social Skills Inventory demonstrated internal validity and test-retest reliability. The experiment was performed from 1998 till 2002. The experiment was performed with 230 students of the Faculty of Sport Education, Lithuanian Academy of Physical Education, whom we divided in experimental group (136 students) and control group (94 students). In 1998 future sport pedagogues were tested. In 2002, the same investigation was repeated. The investigation was provided with the same students. With the help of c2 test it was proved that distribution of the students in experimental group below listed social skills differ statistically significant (p < 0.05) before experiment and after it according to emotional expressivity, emotional sensitivity, social expressivity, social sensitivity. By comparing evaluations of the level of social skills with t test, it is possible to assume that the level of social skills of sport pedagogues in experimental group differs statistically significant (p < 0.05) before experiment and after it according to emotional expressivity, emotional sensitivity, social expressivity, social sensitivity.